PENGARUH RELIGIUSITAS TERHADAP PERILAKU MEMILIH BANK SYARIAH MELALUI KEPERCAYAAN MEREK (Studi Pada Nasabah Bank Syariah di Kota Mataram) - Baiq Handayani Rinuastuti; Sri Darwini; Eka Agustiani; Imanuella Romaputri Andilolo (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2018)
Religion is an invaluable factor in understanding culture as it is the most universal and influential social institution as well as it serves a significant role in attitude, values, and behaviour. There has been a lack of research that includes roles of religion as cultural element in terms of consumer behaviour especially using religiosity as its estimator. This research intents to analyze the relationship between an individual’s level of religiosity towards his/her behaviour in choosing a syariah bank, and to provide deeper understanding of the relation between religiosity, brand trust, and consumer behaviour. Location for the research is Mataram City with 100 respondents. Path analysis result proves that religiosity has a significant positive influence both directly and indirectly on the respondents’ decision to choose syariah banking. This finding supports the need for more understanding of religion as sub-culture, target markets and the importance of brand as company strategy in industrial positioning.